Detecting cosmic rays with the LOFAR radio telescope - Schellart, P; Nelles, A; Buitink, S; Corstanje, A; Enriquez, J; Falcke, H; Frieswijk, W; Horandel, JR; Horneffer, A; James, C; Krause, M; Mevius, M; et al. (2013)
The low frequency array (LOFAR), is the first radio telescope designed with the capability to measure radio emission from cosmic-ray induced air showers in parallel with interferometric observations. In the first ~2 years of observing, 405 cosmic-ray events in the energy range of 1016-1018 eV have been detected in the band from 30-80 MHz. Each of these air showers is registered with up to ~1000 independent antennas resulting in measurements of the radio emission with unprecedented detail. This article describes the dataset, as well as the analysis pipeline, and serves as a reference for future papers based on these data. All steps necessary to achieve a full reconstruction of the electric field at every antenna position are explained, including removal of radio frequency interference, correcting for the antenna response and identification of the pulsed signal. © ESO, 2013.